Human Adipose-Derived Stem Cells on Rapid Prototyped Three-Dimensional Hydroxyapatite/Beta-Tricalcium Phosphate Scaffold. Issue 3 (May 2016) - Canciani, Elena; Dellavia, Claudia; Ferreira, Lorena Maria; Giannasi, Chiara; Carmagnola, Daniela; Carrassi, Antonio; Brini, Anna Teresa
Abstract : Abstract: In the study, we assess a rapid prototyped scaffold composed of 30/70 hydroxyapatite (HA) and beta-tricalcium-phosphate (β-TCP) loaded with human adipose-derived stem cells (hASCs) to determine cell proliferation, differentiation toward osteogenic lineage, adhesion and penetration on/into the scaffold. In this in vitro study, hASCs isolated from fat tissue discarded after plastic surgery were expanded, characterized, and then loaded onto the scaffold. Cells were tested for: viability assay (Alamar Blue at days 3, 7 and Live/Dead at day 32), differentiation index (alkaline phosphatase activity at day 14), scaffold adhesion (standard error of the mean analysis at days 5 and 18), and penetration (ground sections at day 32). All the hASC populations displayed stemness markers and the ability to differentiate toward adipogenic and osteogenic lineages. Cellular vitality increased between 3 and 7 days, and no inhibitory effect by HA/β-TCP was observed. Under osteogenic stimuli, scaffold increased alkaline phosphatase activity of +243% compared with undifferentiated samples. Human adipose-derived stem cells adhered on HA/β-TCP surface through citoplasmatic extensions that occupied the macropores and built networks among them. Human adipose derived stem cells were observed in the core of HA/β-TCP. The current combination of hASCs and HA/β-TCP scaffold provided encouraging results. If authors' data will be confirmed in preclinical models, the present engineering approach could represent an interesting tool in treating large bone defects.